Analysis of the Financial Performance Dynamics of Telecommunications Companies in Indonesia Before, During, and After the Pandemic: Integration of Financial Ratios and Managerial Behavior Theory - Malino, Marlina; Syarifuddin, Syarifuddin; Sudarwadi, Dirarini; Numberi, Camelia Lusandri; Sumari, Jenita (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the financial performance of telecommunications companies listed on the Indonesia Stock Exchange from 2018 to 2023, to assess profitability, solvency, liquidity, and activity ratios as key indicators of financial health and strategic adaptation in a turbulent environment. Employing a descriptive quantitative approach, this research analyzes audited annual reports and applies behavior theory to interpret managerial responses to external shocks, particularly during the COVID-19 pandemic. The sample comprises all listed telecommunications firms in Indonesia, with financial ratio analysis conducted for each year to identify performance trends and variations. Results reveal that profitability and solvency ratios generally declined during the pandemic but exhibited signs of moderate recovery afterward. In contrast, liquidity and activity ratios remained below industry benchmarks for many firms. Notably, only a few companies demonstrated consistent improvements across all indicators, underscoring varied adaptive capacity within the sector. The findings highlight the importance of robust financial management and strategic flexibility in withstanding economic disruptions and maintaining competitiveness. This research enhances both academic and practical understanding by illustrating how financial decision-making reflects behavioral adaptation, and recommends that future studies incorporate qualitative variables and broader analytical models to deepen insights into financial resilience in the telecommunications industry.